Pengaruh metode gampang, asyik dan menyenangkan (Gasing) dalam Pembelajaran Fisika Terhadap Hasil Belajar Peserta Didik Pada Konsep Pengukuran Dikelas XI Madrasah Aliyah Sasa - Irawati Hi. Malan (Peneliti.net, 2022)
This research is an experimental study that aims to determine whether there is an influence of the Easy Fun and Fun method on the physics learning outcomes of students on the concept of measurement in class XI Madrasah Aliyah Sasa, South Ternate City. And how much influence or contribution the method has to the success of learning. This type of research is Quasi-Experimental research. The sample used is a population sample of 21 students. The instrument used is a multiple choice test with 20 questions with a score of 0-1. The results of the calculation state that the average value of students during the pre-test is 36.40 and the average value of the post-test is 79.40. So that the difference between the pre-test and post-test scores is 43.00 or the influence of the Gasing method (Easy, Fun and enjoyable) is 43.00